2013
DOI: 10.1093/eurjhf/hfs206
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the diagnostic capability of cardiac magnetic resonance and endomyocardial biopsy in patients with heart failure

Abstract: Non-invasive CMR demonstrated excellent diagnostic capability for patients with HF and was as effective as or superior to EMB. In particular, the use of CMR in combination with clinical data unrelated to EMB may provide excellent diagnostic accuracy for HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 36 publications
(37 reference statements)
0
46
0
8
Order By: Relevance
“…They found that MRI was superior for diagnosing cardiac sarcoid (75% versus 25%) and ARVC (100% versus 0%), but for myocarditis EMB was superior using a gold standard of both diagnostic techniques plus all available clinical information. 25 This study was limited by small numbers of patients with the various pathogeneses, and future studies should examine the diagnostic and clinical use of MRI compared with EMB in patients who underwent both procedures. Also, we rely solely on review of the medical record to determine both the rationale for EMB in each case and the effect of EMB on the subsequent clinical course.…”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that MRI was superior for diagnosing cardiac sarcoid (75% versus 25%) and ARVC (100% versus 0%), but for myocarditis EMB was superior using a gold standard of both diagnostic techniques plus all available clinical information. 25 This study was limited by small numbers of patients with the various pathogeneses, and future studies should examine the diagnostic and clinical use of MRI compared with EMB in patients who underwent both procedures. Also, we rely solely on review of the medical record to determine both the rationale for EMB in each case and the effect of EMB on the subsequent clinical course.…”
Section: Limitationsmentioning
confidence: 98%
“…We did not collect any MRI data in this cohort, and it is possible that some patients might not have undergone biopsy if a diagnosis was determined by MRI. Yoshida et al 25 recently reported the results of a group of patients who had both a cardiac MRI and an EMB. They found that MRI was superior for diagnosing cardiac sarcoid (75% versus 25%) and ARVC (100% versus 0%), but for myocarditis EMB was superior using a gold standard of both diagnostic techniques plus all available clinical information.…”
Section: Limitationsmentioning
confidence: 99%
“…Na przykład, CMR wraz z oceną LGE pozwala na obrazowanie blizn/włóknienia miokardium i różnicowanie między niedokrwiennym i nieniedokrwiennym tłem HF. Ponadto CMR pozwala na udokumentowanie specyficznego obrazu miokardium w przebiegu zapalenia mięśnia sercowego, amyloidozy, sarkoidozy, choroby Chagasa, choroby Fabry'ego, kardiomiopatii z niescalenia oraz hemochromatozy [91,101,103,104].…”
Section: Rezonans Magnetyczny Sercaunclassified
“…In fact, CMR has shown diagnostic accuracy superior or comparable to that of endomyocardial biopsy (EMB) for the causal characterization of patients with heart failure. 51 Delayed enhancement-MR imaging is also superior to echocardiography in identifying such complications of heart failure as LV thrombus. 52 Perfusion imaging with use of dynamic contrast-enhanced (DCE)-MR can identify modifiable substrate, such as myocardial ischemia.…”
Section: A B Heart Failure and Heart Transplantationmentioning
confidence: 99%